Letter - Lizaso, Jose I. de
1937-07-06 Autonomous Government of Euzkadi London Delegation, Spanish Embassy, 24, Belgrave Square, S.W.1. 6th. July 1937. Dear Sir Walter, The Commercial Office of the Basque Delegation has to-day received information that several steamships chartered by our Government have been stopped by insurgent warships beyond the three mile limit and that British ships have commanded them not to enter the port of Santander on account of its being blockaded. The facts are as follows : - s.s."Latimer": This ship was instructed by British battleships not to enter; it belongs to Finchley Steamship Co.Ltd. "Seven Seas Spray": This ship, which was similarly instructed, belongs to the Veronica Steamship Company. "Gordonia": This ship is the property of the Gordon Steam-ship Co.Ltd. of Newcastle. She was proceeding from Bayonne to Santander for the purpose of transporting refugees and at 9.50 a.m. Greenwich time wirelessed "Stopped by insurgent warship 5 miles N.E. Cabo Mayor". At 10.50 a.m. she sent the following message via the British motor vessel "Dumana" - "Have two of His Majesty's ships alongside now and waiting instructions from the United Kingdom". According to the information received this afternoon, 292/946/11/71(i)